2021
DOI: 10.3389/fonc.2021.713685
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic and Robotic Minimally Invasive Thermal Ablation of Malignant Liver Tumors: A Systematic Review and Meta-Analysis

Abstract: BackgroundStereotactic navigation techniques aim to enhance treatment precision and safety in minimally invasive thermal ablation of liver tumors. We qualitatively reviewed and quantitatively summarized the available literature on procedural and clinical outcomes after stereotactic navigated ablation of malignant liver tumors.MethodsA systematic literature search was performed on procedural and clinical outcomes when using stereotactic or robotic navigation for laparoscopic or percutaneous thermal ablation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 76 publications
2
14
0
Order By: Relevance
“…A handful of studies have shown that traversal of a greater length of lung parenchyma is associated with higher rates of pneumothorax [23][24][25][26], likewise fissure traversal, and ablation zones which encompass pleura [27]. Since all these factors can be influenced by careful multiplanar planning, including Although robotic lung tumor ablation is poorly established in the literature, our results are similar to stereotactic liver ablation, were our Euclidian error of 5.1 mm is very similar to the pooled error of 5.3 mm in a recent meta-analysis [12]. The high level of trust we developed in our technique meant we used smaller array diameter electrodes than in freehand procedures (3.0 vs. 3.5 mm, P = 0.001), without a need for more overlapping ablation zones (P > 0.99), although broad umbrella electrode configuration means a few millimeters of imprecision can usually be tolerated.…”
Section: Discussionsupporting
confidence: 80%
“…A handful of studies have shown that traversal of a greater length of lung parenchyma is associated with higher rates of pneumothorax [23][24][25][26], likewise fissure traversal, and ablation zones which encompass pleura [27]. Since all these factors can be influenced by careful multiplanar planning, including Although robotic lung tumor ablation is poorly established in the literature, our results are similar to stereotactic liver ablation, were our Euclidian error of 5.1 mm is very similar to the pooled error of 5.3 mm in a recent meta-analysis [12]. The high level of trust we developed in our technique meant we used smaller array diameter electrodes than in freehand procedures (3.0 vs. 3.5 mm, P = 0.001), without a need for more overlapping ablation zones (P > 0.99), although broad umbrella electrode configuration means a few millimeters of imprecision can usually be tolerated.…”
Section: Discussionsupporting
confidence: 80%
“…Thermal ablation such as microwave ablation (MWA) is a tissuesparing treatment alternative to hepatic resection in selected patients, yielding similar treatment efficacy, recurrence-free survival, and overall survival as described in non-randomized studies (1)(2)(3)(4)(5). Treatment efficacy can be significantly enhanced by using stereotactic navigation technology for precise targeting of liver tumors as opposed to conventional targeting techniques (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…Possible explanations for the different results of the studies could be the different characteristics of heat generation and distribution in MWA and RFA and, at least in comparison to Wang, the different tumor characteristics of HCC and colorectal liver metastases. Another possible explanation for the differing results could be the use of a stereotactic navigation system in combination with MWA because those methods seem to achieve better results regarding PTE and, respectively, OS in larger HCC lesions [ 32 , 36 , 37 ] settings, where conventional percutaneous ablation techniques show an incline in PTE and prognosis [ 3 ]. Further studies regarding these questions would be of interest.…”
Section: Discussionmentioning
confidence: 99%